Personal Hygiene of Workers in Waste Disposal Site Ponorogo Regency, East Java, Indonesia - Rindang Diannita; Dikri Amarulloh; Eka Rosanti; Muhammad Rifki Taufik (International Journal of Health and Pharmaceutical (IJHP), 2022)
Personal hygiene is useful in maintaining the health of workers. However, Personal Hygiene is considered less important for workers due to the knowledge and attitudes of workers' personal hygiene. One's knowledge will have a positive and negative impact on one's actions. Garbage becomes a source of various diseases if not managed properly. The purpose of this study was to analyze the personal hygiene behavior of waste disposal workers and the factors that influence behavior. The research method is qualitative with a descriptive approach, with a total of 10 informants. Data collection techniques were carried out by in-depth interviews and direct observation. The results of the research on the personal hygiene behavior of workers are very important, knowledge of workers regarding personal hygiene and occupational safety and health is very necessary, by paying more attention to and improving personal hygiene, by maintaining hand hygiene, feet, nails, hair hygiene and maintaining skin hygiene on a regular basis. completing sanitation facilities, increasing management support in the form of occupational safety and health supervision. Managers are expected to be able to apply Occupational Health and Safety and apply personal hygiene behavior in particular.